Perancangan dan Implementasi Simpuh (Sistem Informasi Pemasaran, Keuangan, dan Unit Usaha) untuk Optimalisasi Kinerja BUMDes - Yunanto, Rio; Wahab, Deden Abdul; Anggadini, Sri Dewi; Purfini, Apriani Puti; Yulianto, Hery Dwi (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
BUMDes (Village-Owned Enterprises) as the primary driver of village economy faces challenges in financial management, operations, and marketing that remain largely manual. Limited digital literacy and lack of integrated systems result in slow, inefficient, and non-transparent business processes. The urgency of IT-based digitalization has become critical to enhance governance effectiveness and economic competitiveness at the village level. Main problems include weak financial governance, low human resource competency, and absence of an integrated system unifying financial, production, and marketing functions. This study aims to develop and implement the Management Information System for Marketing, Finance, and Business Units (SIMPUH) as a digital solution to improve efficiency, transparency, and digital transformation at BUMDesma Dana Amanah Pemberdayaan Masyarakat Maja Maju LKD. The research employs Rapid Application Development (RAD) approach with iterative stages including requirements planning, user design, and construction, observations, FGD, and UAT. Results demonstrate a web-based 3-tier system with five integrated modules: Loans, Bottled Water (AMDK), Kiosk, E-commerce, and Dashboard. System implementation yielded 80% improvement in transaction time efficiency, 20% increase in data accuracy, and 85% user adoption rate. Average user satisfaction reached 4.4/5.